Assessment of dental caries experience, periodontal status, and oral mucosal lesions among human immunodeficiency virus seropositives with and without antiretroviral therapy: A cross-sectional study - Vijaya Hegde; Pooja J Shetty; Shubhan Alva; S Kavery Chengappa (Wolters Kluwer Medknow Publications, 2016)
Introduction: Among people living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), studies shows variations in the prevalence of oral manifestations which may be attributed to differences in prescribed medications, stages of disease, way of transmission, and inadequate diet. Aim: To assess the dental caries experience, periodontal status, and oral mucosal lesions among people living with HIV/AIDS. Materials and Methods: A cross-sectional study was conducted for a period of 2 months among 130 people above the age group of 15 years, having HIV/AIDS. Oral mucosal lesions were assessed according to the World Health Organization Oral Health Assessment Form 1997; dental caries was assessed using decayed, missing, and filled teeth (DMFT) index and periodontal status was assessed using community periodontal index of treatment needs index by a single calibrated examiner. Data on antiretroviral therapy (ART) were obtained from medical records. The data were analyzed using SPSS version 16. Level of significance was set at 0.05. Results: Majority of them were females (84.6%), and 86.2% were on ART. There was no significant difference in the DMFT score among subjects with and without ART (median = 3). Fisher's exact test did not show statistically significant difference in the periodontal status between people with or without ART. Hyperpigmentation was found in 12.5% of the study subjects with ART. Conclusions: Subjects with and without ART did not show any difference in the prevalence of dental caries or periodontal status. Hyperpigmentation was the common condition found among subjects with ART. However, further follow-up studies are required to gain insight to the long-term use of ART on oral tissues.